1945
DOI: 10.1037/h0054417
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the nutritional basis of abnormal behavior in albino rats. V. The effect of pyridoxine deficiency upon sound-induced magnesium tetany.

Abstract: Detailed reviews of the role of magnesium in animal nutrition have been made by , Greenberg (20), Duckworth (9), and Maynard and Loosli (39). Of special interest for the present experiments are those studies which have devoted some attention to the symptom complex designated as magnesium tetany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1946
1946
1966
1966

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…The induced and "spontaneous" convulsions observed during the foregoing experiments were similar to those previously described in young rats (5,8,12). Systematic tests revealed a continuum of sensitivity in the magnesium deficient rats with seizure patterns of increasing severity correlated with the advancing stages of deficiency.…”
Section: Discussionsupporting
confidence: 83%
“…The induced and "spontaneous" convulsions observed during the foregoing experiments were similar to those previously described in young rats (5,8,12). Systematic tests revealed a continuum of sensitivity in the magnesium deficient rats with seizure patterns of increasing severity correlated with the advancing stages of deficiency.…”
Section: Discussionsupporting
confidence: 83%
“…rigidly to the sides, while the hind limbs were in extension. Such rigidity seemed similar to that shown by a decerebrate preparation (13). During the tonic phase the pupils were dilated and unresponsive to light.…”
Section: Fig 2 Stages Of Electrically Induced Convulsive Seizuressupporting
confidence: 79%
“…The seizures were either a running attack or a clonic type usually preceded by a running attack. No severe tonic convulsions, such as those that often occur in magnesium deficient rats (7,10) were observed in the B 6 -deficient rats.…”
Section: Experimental Procedubesmentioning
confidence: 85%
“…It has been shown that a long time is required to obtain convulsions in rats fed a diet deficient in B 8 from weaning (2,3,7). Group II shows that even when the mother is fed a deficient diet starting not later than the twelfth day after parturition, the young show only a low and sporadic incidence of seizures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation